The Usage of Collaborative Economy in Tourism: Overview and Trends for European Countries - Tamara Ćurlin; Božidar Jaković; Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Collaborative economy (CE) is the marketplace where individuals trade goods and services. With disruptive innovations as a key factor, CE has is reformulated strategies and methods of traditional global commerce and created new opportunities. Tourism and hospitality are the industries in which is CE used the most, especially at arranging accommodation and transportation. The purpose of this paper is to distinguish the state and trends of CE usage in tourism for European countries by comparing data obtained on Eurostat. In addition, results for accommodation and transport arrangement have been compared. CE usage in tourism has been compared to the frequency of internet usage of individuals in European countries to extract knowledge on factors which may influence on CE usage in European countries. In most countries, the percentage of CE usage in tourism is extensively increasing, which indicates that European travellers have recognised the benefits of CE practices such as more personalised offer and diversification. Results showed a correlation between CE usage in tourism frequency of internet usage and the level of digital skills for individuals from European. That could suggest that the biggest issue for CE development in European countries is poverty and infrastructure. Future research should focus on the empirical testing the correlation of the variables as well as extracting themes for CE usage in order to identify the factor of success in a specific country.
Keywords: O32; 330; collaborative economy; disruptive technologies; tourism; European countries